Preparation method of modified cathode lithium supplement additive material

CN117735617BActive Publication Date: 2026-10-16JIANGXI GANFENG BATTERY TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311828115.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-16
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

[0006]基于此,为了解决背景技术中存在导电性、稳定性较差以及材料表面残余碱含量高的问题,本发明提出了一种改性阴极补锂添加剂材料的制备方法

Benefits of technology

为了达到此发明的目的,本发明提出一种双层核壳结构包覆的C@xLiMbO.yLi5FeO4,其中核体物质为Li5FeO4,第一包覆层为LiMbO,第二包覆层为致密碳层,通过引入M元素氧化物可以在材料烧结过程中吸收表面少量残碱,并形成一层致密的隔离膜,引入第二包覆混合碳层可以提高其稳定性以及导电性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117735617B_ABST
    Figure CN117735617B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a modified cathode lithium supplement additive material, comprising the following steps: S1: uniformly ultrasonically dispersing a soluble iron salt, a high-molecular dispersible surfactant, an antioxidant and an inorganic oxide to obtain solution A; S2: uniformly dispersing a lithium source and a precipitating agent into a saturated solution B through ultrasonic stirring; S3: putting the solution A and the solution B into a high-pressure reaction kettle to perform a solvothermal reaction, performing centrifugal water washing after the reaction is completed, and drying in a protective atmosphere to obtain a single-layer nano-oxide coated LiFeO2 precursor C; and S4: performing high-speed solid-phase mixing of the nano-precursor C, a lithium source and a conductive carbon source, and then performing sectional sintering; in the lithium ferrite preparation method, the sintering of the conductive carbon source and the lithium source through solid-phase mixing can obviously improve the conductive performance of the lithium ferrite material, and the deposition and coating of a hydrophobic layer on the outermost layer of the lithium ferrite through the supplement of a gaseous carbon source in the second sintering process can obviously improve the environmental tolerance of the lithium ferrite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and more specifically, to a method for preparing a modified cathode lithium supplementation additive material. Background Technology

[0002] Lithium-ion batteries are widely used in the energy storage field due to their high specific capacity, high voltage, long cycle life, good thermal stability, no memory effect, and low environmental pollution. They are widely used in some large-scale electric vehicles and energy storage devices.

[0003] During the formation and capacity testing of lithium-ion batteries, the formation of a dense and stable SEI film at the anode-electrolyte interface consumes some lithium ions, leading to a decrease in the initial charge-discharge efficiency of lithium-ion batteries. To solve this problem, cathode active materials are usually mixed with lithium replenishment additives to prepare electrode sheets, thereby improving the efficiency and cycle performance of lithium-ion batteries. Currently, the widely studied cathode lithium replenishment material Li5FeO4 can release four Li ions, has a high capacity, and its anti-fluorite structure results in irreversible delithiation (extremely low initial charge-discharge efficiency), making it an ideal cathode lithium replenishment additive.

[0004] However, Li5FeO4 has extremely poor conductivity and stability, and is very unstable in air. It easily absorbs moisture to form low-activity LiFeO2 and residual alkali on the surface. This not only reduces its electrochemical activity, but the presence of residual alkali can also cause the lithium-ion battery electrode to easily gel during the manufacturing process and generate gas during battery cycling, posing a safety hazard.

[0005] Therefore, the present invention relates to a method for preparing a modified cathode lithium supplementation additive material. Summary of the Invention

[0006] Based on this, in order to solve the problems of poor conductivity and stability and high residual alkali content on the material surface in the background technology, the present invention proposes a method for preparing modified cathode lithium supplementation additive materials.

[0007] The objective and efficacy of this invention are achieved by the following specific technical means: a method for preparing a modified cathode lithium supplementation additive material, comprising the following steps: S1: Soluble iron salt, high molecular weight dispersible surfactant, antioxidant, and inorganic oxide are ultrasonically dispersed evenly to obtain liquid A; S2: Disperse the lithium source, precipitant, and ultrasonically stirred to form a saturated solution B; S3: Solution A and solution B are put into a high-pressure reactor for solvothermal reaction. After the reaction is complete, the mixture is centrifuged and washed with water, and then dried in a protective gas to obtain a single-layer nano-oxide-coated LiFeO2 precursor C. S4: The nano-precursor C was subjected to solid-state high-speed mixing with a lithium source and a conductive carbon source, followed by segmented sintering. The first segment was sintered using an inert gas for phase formation, and the second segment was coated using a gaseous carbon source for surface deposition, ultimately yielding C@xLiMO.yLi5FeO4, where M is one or more elements selected from Al, Co, Mg, F, Ni, Mn, Zn, Cr, and Si, with 0 ≤ Li < 7. <b<5, 0<O<6 ,0<x<0.5, 0.5<y<1。

[0008] Preferably, in step S1, the soluble iron source used is one or a combination of FeSO4, FeCl2, FeC2O4, FeNO3, Fe2(SO4)3, FeCl3, Fe2(C2O4)3, and Fe(NO3)3 iron salts.

[0009] Preferably, in step S1, the Fe2+:Fe3+ molar ratio in the iron salt is 0-1.0.

[0010] Preferably, in step S1, the polymeric dispersant surfactant is one or a combination of sodium dodecyl sulfonate, dodecyltrimethylammonium bromide, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

[0011] Preferably, in step S1, the antioxidant is one or a combination of methanol, ethanol, ethylene glycol, propanol, and glycerol.

[0012] Preferably, in step S1, the inorganic oxide is one or more of MgO, Al2O3, CoO-OH, NH4F, NiO, MnO, ZnO, Cr2O3, and SiO2.

[0013] Preferably, in step S2, the lithium source is one or more of LiOH·H2O, Li2CO3, LiNO3, and Li2O.

[0014] Preferably, in step S2, the Li:Fe molar ratio of the lithium source is 1.00-1.20:1.

[0015] Preferably, in step S2, the precipitant is one or more of NaOH, NH3·H2O, CH4N2O, NH4HCO3, and H2C2O4.

[0016] Preferably, in step S3, the solvothermal high-pressure reaction conditions are 160-220℃ and the reaction time is 10-30h.

[0017] Preferably, in step S4, the added conductive carbon source is one or a combination of multiple of the following: Ketjen black, coconut shell carbon powder, rice husk carbon powder, lychee wood carbon powder, Super-P conductive carbon black, Hi-Black 30 conductive carbon black, carbon nanotubes, graphene, phenolic resin, and polyaniline.

[0018] Preferably, in step S4, the amount of conductive carbon source coating added is 1%-5%.

[0019] Preferably, in step S4, the lithium source is one or more of LiOH·H2O, Li2CO3, LiNO3, and Li2O.

[0020] Preferably, in step S4, the lithium source is added in a lithium-iron molar ratio of Li:Fe = 4.05-4.2:1.

[0021] Preferably, in step S4, the inert gas used for segmented sintering is one of argon, nitrogen, helium, or neon.

[0022] Preferably, in step S4, the gaseous carbon source used in the segmented sintering is one or more of petroleum pitch, petroleum coke, ethylene, and acetylene.

[0023] Preferably, in step S4, the amount of gaseous carbon source coating used in segmented sintering is 0.5%-5%.

[0024] Preferably, in step S4, the sintering temperature of the first stage of the segmented sintering process is 400-600℃, the sintering time is 20-40h, and the sintering temperature of the second stage is 200-400℃.

[0025] The beneficial effects of this invention are: To achieve the purpose of this invention, this invention proposes a double-layer core-shell structure coated C@xLiMbO.yLi5FeO4, wherein the core material is Li5FeO4, the first coating layer is LiMbO, and the second coating layer is a dense carbon layer. By introducing M element oxides, a small amount of residual alkali on the surface can be absorbed during the sintering process of the material, and a dense isolation film can be formed. Introducing the second coating mixed carbon layer can improve its stability and conductivity.

[0026] This invention pre-synthesizes a nano-LiFeO2 precursor, which, after being combined with lithium, undergoes multiple sintering processes to produce a powdered product. This eliminates the need for repeated sintering and pulverization processes, thereby reducing the manufacturing cost.

[0027] In the lithium ferrite preparation method provided by the present invention, an iron source, a lithium source, an inorganic oxide, and a precipitant are mixed and reacted in a solvent using a solvothermal method to obtain an inorganic oxide film with a small particle size to coat LiFeO2 nano precursor material. Then, the conductivity of the lithium ferrite material can be significantly improved by adding a conductive carbon source and a lithium source through solid-phase mixing and sintering. In the second sintering process, the environmental tolerance can be significantly improved by adding a gaseous carbon source to deposit a hydrophobic layer on the outermost layer of the lithium ferrite. Attached Figure Description

[0028] The present invention will be further described below with reference to the accompanying drawings.

[0029] Figure 1 This is a schematic diagram of the double-layer coating structure of the present invention; Figure 2 This is a schematic diagram of the charging curve. Implementation

[0030] To better understand the above-mentioned objects, features, and advantages of the present invention, the following description is provided in conjunction with the accompanying drawings. Figure 1-2 The specific embodiments described below provide a further detailed description of the present invention. The following examples are merely illustrative of implementing the invention. It must be noted that the disclosed embodiments do not limit the scope of the invention. Conversely, any modifications and refinements made without departing from the scope of the invention are within the scope of patent protection of the present invention.

[0031] This invention proposes a double-layer core-shell structure coated C@xLiMbO.yLi5FeO4, wherein the core material is Li5FeO4, the first coating layer is LiMbO, and the second coating layer is a dense carbon layer. By introducing oxides of element M, a small amount of residual alkali on the surface can be absorbed during the sintering process, forming a dense insulating film. Introducing the second coating mixed carbon layer can improve its stability and conductivity. In the preferred embodiment of the above-mentioned cathode lithium supplementation additive, M in the first coating layer is one or more elements selected from Al, Co, Mg, F, Ni, Mn, Zn, Cr, and Si, wherein the number of atoms is 0 ≤ Li < 7. <b<5, 0<o<6, The preferred first coating layer of the above-mentioned cathode lithium supplementation additive C@xLiMbO.yLi5FeO4 has a proportion of 0. <x<0.5, 0.5<y<1 The ratio of the second carbon coating content of the cathode lithium supplement additive to the main material can be (0.005~0.10):1, specifically (0.005~0.01):1, (0.01~0.02):1, (0.02~0.04):1, (0.04~0.08):1, (0.08~0.10):1. A method for preparing a modified cathode lithium supplementation additive material includes the following steps: S1: Soluble iron salt, high molecular weight dispersible surfactant, antioxidant, and inorganic oxide are ultrasonically dispersed evenly to obtain liquid A; In step S1, the soluble iron source used is one or a combination of FeSO4, FeCl2, FeC2O4, FeNO3, Fe2(SO4)3, FeCl3, Fe2(C2O4)3, and Fe(NO3)3 iron salts.

[0032] In step S1, the molar ratio of Fe2+:Fe3+ in the iron salt is 0-1.0.

[0033] In step S1, the polymeric dispersant surfactant is one or more of sodium dodecyl sulfonate, dodecyltrimethylammonium bromide, polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol, with polyvinylpyrrolidone being a preferred dispersant, as it can form a stable dispersion system, thereby achieving effective dispersion and stability.

[0034] In step S1, the antioxidant is one or a combination of methanol, ethanol, ethylene glycol, propanol, and glycerol.

[0035] In step S1, the inorganic oxide is one or more of the following: MgO, Al2O3, CoO-OH, NH4F, NiO, MnO, ZnO, Cr2O3, and SiO2.

[0036] By adding the aforementioned inorganic oxides, the high residual alkali content on the surface of lithium ferrite materials can be improved by combining with the residual alkali. On the other hand, the environmental tolerance of lithium ferrite materials can be improved by the film-forming properties of the oxides themselves.

[0037] S2: Disperse the lithium source, precipitant, and ultrasonically stirred to form a saturated solution B; In step S2, the lithium source is one or more of LiOH.H2O, Li2CO3, LiNO3, and Li2O, with LiOH.H2O being the preferred economical nuclear material.

[0038] In step S2, the molar ratio of lithium source Li:Fe is 1.00-1.20:1.

[0039] In step S2, the precipitant is one or more of NaOH, NH3·H2O, CH4N2O, NH4HCO3, and H2C2O4, with CH4N2O being the preferred choice, as it can slowly release OH- during the solvothermal reaction to obtain precursor nanoparticles with smaller particle size and better uniformity.

[0040] S3: Solution A and solution B are put into a high-pressure reactor for solvothermal reaction. After the reaction is complete, the mixture is centrifuged and washed with water, and then dried in a protective gas to obtain a single-layer nano-oxide-coated LiFeO2 precursor C. In step S3, the solvothermal high-pressure reaction conditions are 160-220℃ and the reaction time is 10-30h. Experimental verification shows that the preferred process conditions are 200℃ for 20h, which can obtain precursor nanoparticles with better particle size uniformity.

[0041] S4: The nano-precursor C was subjected to solid-state high-speed mixing with a lithium source and a conductive carbon source, followed by segmented sintering. The first segment was sintered using an inert gas for phase formation, and the second segment was coated using a gaseous carbon source for surface deposition, ultimately yielding C@xLiMO.yLi5FeO4, where M is one or more elements selected from Al, Co, Mg, F, Ni, Mn, Zn, Cr, and Si, with 0 ≤ Li < 7. <b<5, 0<O<6 ,0<x<0.5, 0.5<y<1。

[0042] In step S4, the added conductive carbon source is one or a combination of Ketjen black, coconut shell carbon powder, rice husk carbon powder, lychee wood carbon powder, Super-P conductive carbon black, Hi-Black 30 conductive carbon black, carbon nanotubes, graphene, phenolic resin, and polyaniline. Experiments have shown that adding an appropriate amount of conductive carbon source can significantly improve the surface conductivity of lithium ferrite materials.

[0043] In step S4, the amount of conductive carbon source coating added is 1%-5%.

[0044] In step S4, the lithium source is one or more of LiOH.H2O, Li2CO3, LiNO3, and Li2O, with LiOH.H2O being the preferred source for economic efficiency and subsequent sintering temperature.

[0045] In step S4, the lithium source is added with a lithium-iron molar ratio of Li:Fe = 4.05-4.2:1.

[0046] In step S4, the inert gas used in the segmented sintering is one of argon, nitrogen, helium, or neon. Among them, nitrogen is the preferred inert atmosphere considering safety, practicality, and economy.

[0047] In step S4, the gaseous carbon source used in the segmented sintering is one or more of petroleum pitch, petroleum coke, ethylene, and acetylene.

[0048] In step S4, the amount of gaseous carbon source coating used in segmented sintering is 0.5%-5%.

[0049] In step S4, the sintering temperature of the first stage of the segmented sintering process is 400-600℃, and the sintering time is 20-40h. The sintering temperature of the second stage is 200-400℃. Example

[0050] This embodiment involves the following steps: FeSO4·7H2O and FeCl3 were mixed at a molar ratio of Fe2+:Fe3+ of 1:2 to prepare a solution of 0.002 mol / ml. Then, SiO2, polyvinylpyrrolidone, and ethylene glycol were added and ultrasonically dispersed to form solution A. Add LiOH·H2O and an appropriate amount of CH4N2O precipitant solution at a Li:Fe ratio of 1.1:1, and ultrasonically disperse to form solution B. Solutions A and B were mixed and added to a polytetrafluoroethylene liner. The mixture was then sealed in a hydrothermal reactor and placed in a forced-air drying oven at 200°C for 20 hours. After the reactor cooled, the reaction solution was centrifuged, washed with water, and dried to obtain the SiO2@LiFeO2 precursor. The precursor obtained above was added to LiOH·H2O at a Li:Fe molar ratio of 4.1:1 and mixed with 1% Ketjen black carbon at high speed. After uniform mixing, the mixture was sintered in stages. The first stage sintering process was carried out under a nitrogen atmosphere with an oxygen concentration of less than 100ppm and sintered at 500℃ for 20h. The second stage sintering process was carried out under the conditions of 500ml / h bituminous petroleum gas and sintered at 380℃ for 2h. A cathode lithium supplementation additive material was prepared with the chemical formula C@0.05Li2SiO3.0.95Li5FeO4. The material has a double-layer structure of lithium ferrite, with the outermost layer being a mixed carbon layer and the second layer being Li2SiO3. Its specific charging capacity is 684mAh, its powder resistivity is 2.5Ω·cm, and its moisture absorption value is 1.85ppm / s. Example

[0051] This embodiment is achieved through the following steps: FeCl3·7H2O was prepared into a 0.002 mol / ml solution, and then Co(OH)2, polyethylene glycol, and ethylene glycol were added and ultrasonically dispersed to form solution A. Add LiOH·H2O and an appropriate amount of precipitant NH4HCO3 at a Li:Fe ratio of 1.2:1, and ultrasonically disperse to form solution B. Solutions A and B were mixed and added to a polytetrafluoroethylene liner. The mixture was then sealed in a hydrothermal reactor and placed in a forced-air drying oven at 220°C for 20 hours. After the reactor cooled, the reaction solution was centrifuged, washed with water, and dried to obtain the CoO@LiFeO2 precursor. Add LiOH·H2O and an appropriate amount of precipitant NH4HCO3 at a Li:Fe ratio of 1.1:1 and ultrasonically disperse to form solution B; Solutions A and B were mixed and added to a polytetrafluoroethylene liner. The mixture was then sealed in a hydrothermal reactor and placed in a forced-air drying oven at 200°C for 20 hours. After the reactor cooled, the reaction solution was centrifuged, washed with water, and dried to obtain the CoO@LiFeO2 precursor. The precursor obtained above was added to LiOH·H2O at a Li:Fe molar ratio of 4.2:1 and 1% carbon nanotubes and mixed at high speed until uniform. Then, it was sintered in stages. The first stage sintering process was carried out under a nitrogen atmosphere with an oxygen concentration of less than 100ppm and sintered at 500℃ for 20h. The second stage sintering process was carried out under the following conditions: ethylene gas was introduced at 100ml / h and sintered at 300℃ for 5h. A cathode lithium supplementation additive material was prepared with the chemical formula C@0.05Li6CoO4.0.95Li5FeO4. The material has a double-layer structure of lithium ferrite, with the outermost layer being a mixed carbon layer and the second layer being Li6CoO4. Its specific capacity is 725mAh, its powder resistivity is 1.5Ω·cm, and its moisture absorption value is 1.58ppm / s. Example

[0052] This embodiment involves the following steps: FeSO4·7H2O and FeCl3 were prepared into a 0.002 mol / ml solution at a molar ratio of Fe2+:Fe3+ of 1:2. Then Al2O3, sodium dodecyl sulfonate and ethanol were added and ultrasonically dispersed to form solution A. Add LiOH·H2O and an appropriate amount of precipitant NH4HCO3 at a Li:Fe ratio of 1.05:1, and ultrasonically disperse to form solution B. Solutions A and B were mixed and added to a polytetrafluoroethylene liner. The mixture was then sealed in a hydrothermal reactor and placed in a forced-air drying oven at 200°C for 20 hours. After the reactor cooled, the reaction solution was centrifuged, washed with water, and dried to obtain the CoO@LiFeO2 precursor. Add LiOH·H2O and an appropriate amount of precipitant NH4HCO3 at a Li:Fe ratio of 1.1:1 and ultrasonically disperse to form solution B; Solutions A and B were mixed and added to a polytetrafluoroethylene liner. The mixture was then sealed in a hydrothermal reactor and placed in a forced-air drying oven at 200°C for 20 hours. After the reactor cooled, the reaction solution was centrifuged, washed with water, and dried to obtain the CoO@LiFeO2 precursor. (5) The precursor obtained above was added to LiOH.H2O at a Li:Fe molar ratio of 4.2:1 and 1% Ketjen black carbon and mixed evenly at high speed. The first stage of sintering was carried out at 500℃ for 20h under a nitrogen atmosphere with an oxygen concentration of less than 100ppm. The second stage of sintering was carried out at 380℃ for 2h with 500ml / h asphalt petroleum gas introduced. A cathode lithium supplementation additive material was prepared with the chemical formula C@0.05Al2O3.0.95Li5FeO4. The material has a double-layer structure of lithium ferrite, with the outermost layer being a mixed carbon layer and the second layer being Al2O3. Its specific capacity is 704mAh, its powder resistivity is 2.0Ω·cm, and its moisture absorption value is 1.38ppm / s.

[0053] Comparative Example 1 This comparative example is obtained through the following steps. FeO3 was used as a precursor, and lithium hydroxide monohydrate was added at a Li:Fe ratio of 5.1:1. Super-P conductive carbon black was added at 2% of the theoretical finished product mass and then mixed at high speed.

[0054] The above mixture was subjected to a first high-temperature sintering in a nitrogen atmosphere at 600℃ for 30 hours. The first sintered product was then pulverized, mixed thoroughly, and subjected to a second high-temperature sintering in a nitrogen atmosphere at 450℃ for 20 hours. The product was then pulverized again to obtain the C@Li5FeO4 finished material. A single-layer carbon-coated Li5FeO4 with the chemical formula C@Li5FeO4 was prepared. The material has a specific capacity of 580 mAh, a moisture absorption value of 136 ppm / s, and a powder resistivity of 1258 Ω·cm.

[0055] Table 1: This invention mainly analyzes the stability and conductivity of modified lithium ferrite materials by testing the resistivity of the powder, residual alkali on the surface, charging capacity, and moisture absorption value of the materials.

[0056] Comparing the overall performance of the examples and comparative examples in Table 1, the comparative example, lacking an oxide layer coating on Li5FeO4, exhibits higher residual alkali on its surface, easily leading to gelation during subsequent cell fabrication. Furthermore, the outermost layer lacks a mixed carbon source coating, resulting in significantly higher moisture absorption values ​​at dew points. This demonstrates that a single conductive carbon layer coating only improves the material's conductivity but does not effectively enhance its environmental tolerance, still exhibiting easy decomposition at dew points, posing significant challenges to subsequent cell fabrication. Moreover, from... Figure 2 The charging curve also shows that the final charging capacity is only 580mAh, while in Example 2, the improved conductivity and stability of the device through the modification technology of this invention ultimately resulted in a final charging capacity of 720mAh.

Claims

1. A method for preparing a modified cathode lithium supplementation additive material, characterized in that, Includes the following steps: S1: Soluble iron salt, high molecular weight dispersible surfactant, antioxidant and inorganic oxide are ultrasonically dispersed evenly to obtain liquid A; S2: Ultrasonically disperse the lithium source and precipitant into solution B; S3: Add solution A and solution B together into a high-pressure reactor for a solvothermal reaction. After the reaction is complete, centrifuge and wash with water, and dry in a protective gas to obtain a single-layer nano-oxide-coated LiFeO2 precursor C. S4: subjecting precursor C, a lithium source and a conductive carbon source to solid-phase high-speed mixing, followed by segmented sintering; the first segment is sintered in an inert gas atmosphere for phase formation, and the second segment adopts a gaseous carbon source for surface deposition and coating, to finally obtain C@xLiM b O·yLi₅FeO₄, M is one or a combination of more elements selected from Al, Co, Mg, Ni, Mn, Zn, Cr and Si, wherein 0.05<x<0.5, 0.5<y<0.95; the number of atoms satisfies 0≤Li<7, 0<b<5, 0<O<6; in step S4, the coating amount of the added conductive carbon source is 1% to 5%; the coating amount of the gaseous carbon source used in the segmented sintering is 0.5% to 5%; In step S2, the precipitant is one or a combination of NaOH, NH3·H2O, NH4HCO3, and H2C2O4; in step S4, the sintering temperature of the first stage of the segmented sintering process is 400-600℃, the sintering time is 20-40h, and the sintering temperature of the second stage is 200-400℃.

2. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S1, the soluble iron salt used is one or a combination of FeSO4, FeCl2, FeNO3, Fe2(SO4)3, FeCl3, and Fe(NO3)3.

3. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S1, the Fe in the iron salt 2+ :Fe 3+ The molar ratio is 0-1.

0.

4. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S1, the polymeric dispersing surfactant is one or more of polyethylene glycol, polyvinylpyrrolidone, and polyvinyl alcohol.

5. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S1, the antioxidant is one or more of methanol, ethanol, ethylene glycol, propanol, and glycerol.

6. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S1, the inorganic oxide is one or more of MgO, Al2O3, NiO, MnO, ZnO, Cr2O3, and SiO2.

7. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S2, the lithium source is one or more of LiOH·H2O, Li2CO3, LiNO3, and Li2O.

8. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S2, the molar ratio of Li to Fe in the lithium source is 1.00 to 1.20:

1.

9. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S3, the solvothermal high-pressure reaction conditions are 160–220°C at a temperature of 10–30 h for a reaction time of 10–30 h.

10. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S4, the conductive carbon source is one or a combination of multiple of the following: Ketjen black, coconut shell carbon powder, rice husk carbon powder, lychee wood carbon powder, Super-P conductive carbon black, carbon nanotubes, graphene, phenolic resin, and polyaniline.

11. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S4, the lithium source is one or more of LiOH·H2O, Li2CO3, LiNO3, and Li2O.

12. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S4, the molar ratio of lithium to iron in the lithium source is Li:Fe = 4.05 to 4.2:

1.

13. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S4, the inert gas used for segmented sintering is one of argon, nitrogen, helium, or neon.

14. The method for preparing a modified cathode lithium supplementation additive material according to claim 1, characterized in that: In step S4, the gaseous carbon source used in the segmented sintering is one or more of ethylene and acetylene.

Citation Information

Patent Citations

  • Superfine high-dispersion super-paramagnetism ferrate nano particles and preparation method thereof

    CN102583567A

  • Modified positive electrode lithium supplementing material and preparation method and application thereof

    CN114242939A

  • Lithium supplement material for positive electrode of lithium ion battery, positive electrode plate of lithium ion battery and lithium ion battery

    CN116565171A